PENGARUH PEMBELAJARAN ONLINE TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS DI SD NEGERI 227 INPRES TAKALAR II KECAMATAN MAPPAKASUNGGU KABUPATEN TAKALAR - Rahmawati; Abdul Aziz Muslimin; Idawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The influence of online learning on students' motivation and learning outcomes in social science learning subjects was conducted by Muslimin and Idawati. The study in this article is designed to 1) determine students’ learning motivation by online learning in social science learning subjects, 2) to find out students’ learning outcomes by online learning in social science learning subjects, and 3) to determine the effect of online learning on students’ motivation and learning outcomes in social science learning subjects. The type of study was descriptive quantitative design. The population involved 110 students at SDN 227 Inpres Takalar II, while the sample involved 51 students at a high-class level. Data collection techniques used were questionnaires and documentation. The data analysis technique used was the path regression analysis technique assisted by SPSS Version 24 for windows. The results of the study indicated that 1) students’ learning motivation by online learning in social science learning subjects was categorized as very good, 2) students’ learning outcomes by online learning in social science learning subjects were still classified as quite good, 3)based on the results of hypothesis testing, it was obtained an R value of the learning motivation variable that indicated a value of 0.079 or 7.9%, which meant that learning motivation was influenced by online learning with a percentage of 7.9%. And the R Square value of the learning outcomes variable indicated a value of 0.001 or 0.1%, which meant that learning outcomes were influenced by online learning.